2013
DOI: 10.1177/0269881113509904
|View full text |Cite
|
Sign up to set email alerts
|

The effect of naltrexone on body fat mass in olanzapine-treated schizophrenic or schizoaffective patients: A randomized double-blind placebo-controlled pilot study

Abstract: Olanzapine (OLZ), a commonly prescribed second generation antipsychotic drug, is associated with obesity and metabolic syndrome and may contribute to increased cardiovascular morbidity and mortality. Opioidergic neurotransmission may be implicated in the development of these metabolic disturbances. The objective of this study was to assess the effects of opioid blockade on OLZ-treated patients' metabolic status. Patients with schizophrenia or schizoaffective disorder (n=30) on a stable dose of OLZ were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
(40 reference statements)
1
27
0
Order By: Relevance
“…Participants' characteristics are detailed in Table , including mean daily dose and duration of olanzapine. Further participants' selection methodology and clinical trial data of some of these participants are reported elsewhere (Taveira et al, ).…”
Section: Methodssupporting
confidence: 93%
“…Participants' characteristics are detailed in Table , including mean daily dose and duration of olanzapine. Further participants' selection methodology and clinical trial data of some of these participants are reported elsewhere (Taveira et al, ).…”
Section: Methodssupporting
confidence: 93%
“…Antagonism at this serotonin receptor increases appetite, which might explain the antipsychotic treatmentinduced weight gain [78]. Second-generation antipsychotics have also been hypothesized to induce weight gain by different mechanisms: (1) contributing to decreased energy expenditure; (2) enhancing the opioidergic activity which could further deteriorate the preexisting hedonic alterations in schizophrenia patients [79]; (3) altering the function of lateral hypothalamic serotonin and/or histamine medidated actions [80]; (4) inducing dopamine antagonists; (5) altering glucose uptake by blocking glucose accumulation directly at the level of the glucose transporter (GLUT) protein in cells derived from both peripheral and brain tissue [81]; (6) inducing insulin resistance and impairments in insulin secretion directly [82,83], and (7) promoting triglyceride accumulation by stimulating lipogenesis and inhibiting lipolysis [74]. Second-generation antipsychotics also target the deregulated HPA axis.…”
Section: Obesity and Schizophreniamentioning
confidence: 99%
“…While it is not possible to exclude other mechanisms of weight loss with naltrexone, it is helpful to note that naltrexone alone does not produce appreciable weight loss in obese/overweight individuals who are not on antipsychotic medications [43] . Also it is interesting to note that the partially negative study by Taveira et al recruited only subjects on olanzapine, an antipsychotic with relatively low D2 and very strong H1 blockade [32] . This may indirectly support the working hypothesis of this paper, that naltrexone might counteract the D2 blockade-related portion of antipsychotic induced weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…This may indirectly support the working hypothesis of this paper, that naltrexone might counteract the D2 blockade-related portion of antipsychotic induced weight gain. On the other hand, Taviera et al showed a decrease in fat mass, and since both groups lost weight, presumably due to nutritional counseling provided, it might be hard to discern differences in naltrexone and placebo groups [32] . Clearly studies with larger sample sizes are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation